Taking a Closer Look at the Factors That Influence Ethnic Identity. Issue 2 (15th March 2017) - Holt, Lanier F.; Hovick, Shelly R.; Fete, Emma M.; Dailey, Phokeng M.
Abstract : Ethnic identity (EI) has long been known to supersede race as a predictor for attitudes and behaviors. However, little is known about the constituent parts that comprise and influence ethnic identity. In order to improve communications that target EI, we examine both demographic and communication variables to determine which have a greater pull on people's attitudes and actions. Race appears to moderate the effects of age on ethnic identity, whereby age was negatively related to ethnic-identity exploration among White participants and positively related to ethnic identity commitment among Black participants ( p < .05). Having a higher income, print-media use, and information-engagement orientation were also positively correlated with ethnic identity; education and gender were not. Implications and future directions are discussed.